One cell-specific and three ubiquitous nuclear proteins bind in vitro to overlapping motifs in the domain B1 of the SV40 enhancer. - Xiao, J H (1987)
We have used the gel retardation assay to investigate the binding of nuclear proteins to the domain B1 of the SV40 enhancer, which contains the GT-II motif. Four proteins (GT-IIA, GT-IIB alpha, GT-IIB beta and GT-IIC) were detected, three of which were present in nuclear extracts from several cell lines. The fourth protein (GT-IIC) showed a clear cell-specificity, being absent from the lymphoid cell extracts tested. The results of methylation interference assays and of the binding of the proteins to mutated templates indicate that the domain B1 contains three distinct, but overlapping, protein-binding motifs (GT-IIA, B and C). The cell-specific binding of protein GT-IIC in vitro correlates with the in vivo enhancer activity of its cognate motif, strongly suggesting that this protein acts as a positive trans-acting enhancer factor. Two of the proteins also recognize other enhancer motifs; protein GT-IIB alpha binds to the microE3 motif present in the immunoglobulin heavy chain enhancer; protein GT-IIC binds to an enhancer motif of the polyomavirus mutant PyEC9.1 adapted to growth in F9 embryonal carcinoma cells, but not to the corresponding wild-type sequence.